Lactic Acidosis Promotes Mitochondrial Biogenesis in Lung Adenocarcinoma Cells, Supporting Proliferation Under Normoxia or Survival Under Hypoxia - Romero-Garcia, Susana; Prado-Garcia, Heriberto; Valencia-Camargo, Alma Delia; Alvarez-Pulido, Abraham (Frontiers in Oncology, 2019)
Lactic acidosis, glucose deprivation and hypoxia are conditions frequently found in solid tumors because, among other reasons, tumors switch to Warburg effect and secrete high levels of lactate, which decreases the pH (<6.9) in the microenvironment. We hypothesized that lung cancer cells consume lactate and induce mitochondrial biogenesis to support survival and proliferation in lactic acidosis with glucose deprivation even under hypoxia. We examined lung adenocarcinoma cell lines (A-427 and A-549), a breast cancer cell line (MCF-7) and non-transformed fibroblasts (MRC-5). Cells were cultured using RPMI-1640 medium with 28 mM lactate varying pH (6.2 or 7.2) under normoxia (atmospheric O2) or hypoxia (2% O2). Cellular growth was followed during 96 h, as well as lactate, glutamine and glutamate levels, which were measured using a biochemical analyzer. The expression levels of monocarboxylate transporters (MCT1 and MCT4) were evaluated by flow cytometry. To evaluate mitochondrial biogenesis, mitochondrial mass was analyzed by flow cytometry and epifluorescence microscopy. Also, mitochondrial DNA (mtDNA) was measured by qPCR. Transcript levels of Nuclear Respiratory Factors (NRF-1 and NRF-2) and Transcription Factor A Mitochondrial (TFAM) were determined using RT-qPCR. The specific growth rate of A-549 and A-427 cells increased in lactic acidosis compared with neutral lactosis, either under normoxia or hypoxia, a phenomenon that was not observed in MRC-5 fibroblasts. Under hypoxia, A-427 and MCF-7 cells did not survive in neutral lactosis but survived in lactic acidosis. Under lactic acidosis, A-427 and MCF-7 cells increased MCT1 levels, reduced MCT4 levels and consumed higher lactate amounts, while A-549 cells consumed glutamine and decreased MCT1 and MCT4 levels with respect to neutral lactosis condition. Lactic acidosis, either under normoxia or hypoxia, increased mitochondrial mass and mtDNA levels compared with neutral lactosis in all tumor cells but not in fibroblasts. A-549 and MCF-7 cells had increased levels of NRF-1, NRF-2 and TFAM with respect to MRC-5 cells, whereas A-427 cells upregulated these transcripts under lactic acidosis compared with neutral lactosis. Thus, lung adenocarcinoma cells induce mitochondrial biogenesis to support survival and proliferation in lactic acidosis with glucose deprivation.